Unfolding the Role of Bureaucracy and a Setback to the Parliamentary Democracy in Pakistan from1947 to 1951 - Haider, Zulqarnain; Abbas Khan, Amjad (Al-Amīr Research Journal for Islamic Studies, 2023)
Institutions are essential organs of the state and bureaucracy is one of these which is considered as the backbone of polity of the particular state. Pakistan inherited the British trained bureaucracy, the only trained institution which they left behind them. In the early years of freedom, state came under stormy environment and the bureaucrats were holding the steering wheel of country’s fate. They were supposed to keep themselves away from political landscape unless and until the country had attained stability. However, due to institutional clashes and corrupt practices, the bureaucrats remained the part of political scenario of the state and resultantly provided a safe road map to military personnel to intervene in the political arena of the country due to which the country had to face a democratic downfall and it paved the way for Martial Law on 7th October, 1958. The study has analyzed the parliamentary democracy in Pakistan and role of bureaucracy in the political landscape of the Pakistan from 1947-1951 It has elaborated all the implications which had transferred the political system of Pakistan from bad to the worst. Keywords: Pakistan, Bureaucracy, Parliamentary Democracy, Administration, Civil Services.